RIVER AND SEA TRANSPORTS IN ROMANIA IN THE EUROPEAN UNION STRATEGY FOR THE DANUBE REGION PERSPECTIVE - RADU SĂGEATĂ (Revue Roumaine de Géographie)
Romania’s geographical position links it essentially to the Black Sea, which thus becomes the main gateway to Europe (through the ports of Constanţa, Constanţa Sud – Agigea and the Danube – Black Sea Canal, unfortunately still not exploited at its full strategic capacity) and the main Caspian-Pontic interface with the West. Situated in the central zone of the geopolitical system of intra-continental seas, Romania can become the “Eastern key” to NATO and EU relationships with Russia, Asia and the Arab states. In this period of searches determined by the globalisation process, Romania possesses the necessary infrastructure to take over, store and transport the energy resources, it being a real partner in the alliances it belongs to. A founder, together with Bulgaria, Georgia, Russia, Turkey and Ukraine, of the Black Sea Economic Community (BSEC), Romania has been actively involved in strengthening trade relations, public and telecomunication works and environmental protection (especially of the Danube Delta, tensioning its relations with Ukraine), stimulating cultural exchanges and granting political support to the Republic of Moldova, Ukraine, Georgia, Azerbaijan and Turkey on the world stage.